Androgen receptor gene CAG-trinucleotide repeat length affects function of endothelium in men with hypogonadism and type 2 diabetes mellitus - I. A. Khripun; R. S. Ismailov; I. I. Belousov; Kh. S. Ibishev; M. I. Kogan (Вестник урологии)
Introduction. The influence of the length of the number of CAG repeats in the androgen receptor gene (nCAG AR) on endothelial dysfunction (EnD) is currently understudied.Objective. The study aimed to evaluate the relationship between the nCAG AR and the dynamics of biochemical and ultrasound markers of EnD in men with functional hypogonadism and type 2 diabetes mellitus (T2DM) receiving testosterone replacement therapy (TRT).Materials & methods. This study included 45 hypogonadal men with T2DM, receiving TRT for 1 year. Patients were assessed for carbohydrate and lipid metabolism parameters; total and free T; sex hormone-binding globulin; biochemical markers of EnD (NO, eNOS3, endothelin) and the nCAG AR; brachial artery (BA) vasoreactivity. Patients were divided into 3 groups: group I — 9 men with nCAG AR < 19; group II — 27 men with nCAG AR > 19 – 24; and group III — 9 men with nCAG AR >24.Results. Patients with nCAG AR < 19 exhibited a 2-fold greater and faster increase in BA vasoreactivity on TRT compared to patients with nCAG AR 19-24 and 3-fold greater than men with nCAG AR >24 (p < 0.05). Patients with nCAG AR < 19 also demonstrated the most pronounced rise in NO and eNOS3 on TRT compared to men with nCAG AR > 24. Patients with nCAG AR < 19 experienced the most pronounced decreases in weight, waist circumference, and HbA1c on TRT compared to other patients (p < 0.05).Conclusion. The nCAG AR length significantly affects the response to TRT in men with hypogonadism and T2DM. The most significant improvements are seen in patients with short nCAG AR.